Coleopteran and Lepidopteran Hosts of the Entomopathogenic Genus Cordyceps sensu lato. (22nd February 2016) - Shrestha, Bhushan; Tanaka, Eiji; Hyun, Min Woo; Han, Jae-Gu; Kim, Chang Sun; Jo, Jong Won; Han, Sang-Kuk; Oh, Junsang; Sung, Gi-Ho
Abstract : Entomophthoralean and ascomycetous fungi are the two major groups known to parasitize arthropods in almost every terrestrial habitat of the earth. Within Ascomycota, Cordyceps sensu lato is a large genus with more than 400 spp. described on numerous orders of Arthropoda. Among the hosts of Cordyceps, Coleoptera and Lepidoptera are the two major orders. Out of the estimated 200 Cordyceps spp. recorded on coleopteran and lepidopteran hosts, we have documented 92 spp. based on the available information of their host species. Among coleopteran hosts, Scarabaeidae and Elateridae are the two major families. Similarly, among lepidopterans, Hepialidae is the largest host family. Cordyceps militaris shows the widest host range, extending to 2 orders, 13 families, and 32 spp. We hope such accumulative work will be useful as a quick reference for interested biologists, forest ecologists, biocontrol researchers, and fungal and insect taxonomists to apprehend host range and host specificities of Cordyceps fungi.